2007
DOI: 10.1590/s1413-81232007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Transferência condicionada de renda e segurança alimentar e nutricional

Abstract: This paper analyses the relationship between Conditional Cash Transfer (CCT) programs and Food and Nutrition Security (FNS),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
57

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 1 publication
0
13
0
57
Order By: Relevance
“…While acknowledging that many factors affect nutritional status, and more specifically infant growth, the effect of conditional cash transfer programmes has been discussed, given that a considerable proportion of the funds transferred is destined for the purchase of food and to meet health care demands, due to conditions existing in these programs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…While acknowledging that many factors affect nutritional status, and more specifically infant growth, the effect of conditional cash transfer programmes has been discussed, given that a considerable proportion of the funds transferred is destined for the purchase of food and to meet health care demands, due to conditions existing in these programs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Os instrumentos (FAO, 2009) utilizados na coleta dos dados foram elaborados com base nos documentos oficiais que normatizam o programa (Brasil, 2004(Brasil, , 2006(Brasil, , 2009b, na literatura científica da área (Castiñeira e col., 2009;Oliveira e col., 2011;Burlandy, 2007;Pereira e col., 2008;Ibase, 2008; Lavinas e col., 2000; Monnerat e col., 2007; Shimizu e Reis, 2011) e nas discussões com representantes da CGAN.…”
Section: Materiais E Métodosunclassified
“…Alguns estudos têm destacado pontos positivos do programa, sobretudo quanto à redução da pobreza, ao aumento do acesso a alimentos (em decorrência do aumento do poder de compra) e ao aumento da frequência tanto nas escolas (pelas crianças) quanto nos serviços de saúde, em virtude das condicionalidades atribuídas às famílias (Castiñeira e col., 2009; Oliveira e col., 2011; Silva, 2007;Burlandy, 2007;Magalhães, 2008;Pereira e col., 2008;Ibase, 2008;Rocha e col., 2011;Minujín e col., 2007). Em contraponto, alguns autores acreditam que a desigualdade não foi reduzida no Brasil, que o PBF ainda não conseguiu erradicar a pobreza (AFP, 2006;Silva, 2007) e que as condicionalidades exigidas às famílias beneficiárias ameaçam os princípios de cidadania (Lavinas e col., 2000).…”
Section: Introductionunclassified
“…Studies have confirmed the impact of the PBF on the reduction of poverty, social inequality, and hunger [2][3][4] . Between 2002 and 2013, Brazil reduced by 82% the undernourished population, exiting the world hunger map.…”
Section: Introductionmentioning
confidence: 98%
“…The Bolsa Família Program (PBF) appears as the central point in the intersectoral agenda of the Brazilian government to promote Food and Nutrition Security (FNS) and the social inclusion of low-income families who remained invisible for many years 1,2 .…”
Section: Introductionmentioning
confidence: 99%